Power and knowledge in Southeast Asia state and scholars in Indonesia and the Philippines - Curaming, Rommel Argamosa 1970- (Abingdon, Oxon Routledge, 2020)
"Examining two state-sponsored history writing projects in Indonesia and the Philippines in the 1970s, this book illuminates the contents and contexts of the two projects and, more importantly, provides a nuanced characterization of the relationship between embodiments of power (state, dictators, government officials) and knowledge (intellectuals, historians, history). Known respectively as Sejarah Nasional Indonesia (SNI) and the Tadhana Project, these projects were initiated by the Suharto and Marcos authoritarian regimes against the backdrop of rising and competing nationalisms, as well as the regimes' efforts at political consolidation. The dialectics between actors and the politico-academic contexts determine whether scholarship and politics would clash, mutually support, or co-exist parallel with one another. Rather than one side manipulating or co-opting the other, this study shows the mutual need or partnership between scholars and political actors in these projects. This book proposes the need to embrace rather than deny the entwined power/knowledge if the idea is for scholarship to realize its truly progressive visions. Analyzing the dynamics of state-scholars relations in the two countries, the book will be of interest to academics in the fields on Southeast Asian history and politics, nationalism, historiography, intellectual history and the sociology of knowledge"--
Introduction : Power and Knowledge -- Indonesia and the Philippines : A Contextual Comparison -- Genesis of the Tadhana Project -- Tadhana in Political and Historiographic Contexts -- The Making of the Sejarah Nasional Indonesia (SNI) -- SNI : Contents and Contexts -- The Calculus of Power-Knowledge Relations
Includes bibliographical references and index.
Keywords: Historiography -- Political aspects -- Indonesia; Historiography -- Political aspects -- Philippines; History -- Political aspects -- Indonesia; History -- Political aspects -- Philippines; Indonesia -- History; Philippines -- History; Indonesia -- Historiography -- Political aspects; Philippines -- Historiography -- Political aspects